Antimicrobial activity, physical, mechanical and barrier properties of sugar palm based nanocellulose/starch biocomposite films incorporated with cinnamon essential oil - Razali, Mohamad Omar Syafiq; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri (Elsevier, 2021)
The demand of antimicrobial active packaging is escalating due to the needs of improving quality and shelf life of food. In this work, sugar palm starch (SPS)/sugar palm nanocrystalline cellulose (SPNCC) incorporated with cinnamon essential oil (EO) biodegradable nanocomposite films were prepared by using solvent casting method. Mechanical properties test revealed that films incorporated with cinnamon EO showed improved tensile strength and tensile modulus values from 4.8 to 5.3 MPa and 122.49–130.52 MPa respectively. Additionally, the density and moisture content were reduced from 1.38 to 1.31 g/cm3 and from 13.65 to 12.33% respectively. The antimicrobial test was carried out by agar disc method (ADM) to evaluate the inhibition effect of the films on the gram positive bacteria, gram negative bacteria and yeast. The result suggested that The higher the amount of EO used (2.0 wt) yielded, the higher the inhibition zone occurred for B. subtilis, S. aereus and E. coli, which were 7.85, 6.63, and 7.43 mm respectively. Overall, cinnamon EO incorporated SPS/SPNCC biodegradable nanocomposite film is a good candidate as an alternative for active packaging material.